Pharmacodynamic Interactions: Mechanisms, Clinical Trial Insights, and Patent Perspectives - Narwal, Smita; Dushyant; Singh, Gurvirender; Grewal, Nisha; Chanalia, Vishal; Dhingra, Ashwani K. (Current Topics in Medicinal Chemistry, 2025)
Pharmacodynamic interactions are relevant in improving drug efficiency without a significant increase in the effects due to toxicity and, in most, are associated with polypharmacy. Mechanisms that govern pharmacodynamic interactions are additive, synergistic, and also antagonistic. Additive drug interactions refer to effects similar to a summation of effects resulting from administering a pair of drugs or a series, while synergistic describes a heightened response much above what one might have aspired to in light of expectations about additivity. However, the antagonistic effect may weaken therapeutic activity at times. Mechanistic pathways like receptor binding, enzyme inhibition, and modulation of signaling pathways were also studied to bring out their relevance in clinical applications. The manuscript is conscious of the role of patents and clinical trials in understanding pharmacodynamic interactions. Patents provide insight into new drug combinations and mechanisms, and the same interaction gets validated through the outcome of clinical trials. Examples that prove clinical relevance have emerged through the synergy in the usage of the drugs for oncology, cisplatin and etoposide, or the additive effect of aspirin and clopidogrel in preventing thrombotic events. The transformative approaches applied in developing drugs include network pharmacology, epigenetics, and receptor crosstalk. In this review, the pharmacodynamic interactions, by integrating mechanistic insights with clinical data, patents, and case studies, explicitly underpin pharmacodynamic interactions as a factor that enhances drug safety, efficacy, and therapeutic precision.
Keywords: additive